2015
DOI: 10.1155/2015/790839
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Heat Transfer and Pressure Drop of CuO‐Water Nanofluid

Abstract: Heat transfer and pressure drop characteristics of water based CuO nanofluid inside a horizontal tube were investigated experimentally. The upper limitation of the particle volume fraction with respect to heat transfer performance was also found. CuO-water nanofluids with volume fractions of 0.5%, 1%, 2%, and 4% were prepared by dispersing the CuO nanoparticles with an average diameter of 33 nm into deionised water. Experiments were carried out under the steady-state, constant heat flux, and turbulent flow reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Bearing in mind that this is a transitional region, this compliance can be considered satisfactory. As shown in Figure 10b, agreement between average Nu number determined by Sahin et al [113] and Zarringhalam et al [130] is very good.…”
Section: Water-cuo Nanofluidssupporting
confidence: 68%
See 1 more Smart Citation
“…Bearing in mind that this is a transitional region, this compliance can be considered satisfactory. As shown in Figure 10b, agreement between average Nu number determined by Sahin et al [113] and Zarringhalam et al [130] is very good.…”
Section: Water-cuo Nanofluidssupporting
confidence: 68%
“…The researchers determined that the Nu number reached the optimum for the moderate Re number, for which it was slightly higher than for the base fluid, and for larger and smaller Re numbers it was lower than for the base fluid by about 8%. Sahin et al [113] observed the optimum NPs concentration above which Nu number decreased for turbulent flow. In addition, they determined the optimum Re number for which the increase in the Nu number was the highest-about 20%.…”
Section: Characteristics Of the Conducted Researchmentioning
confidence: 99%
“…Mixtures of nanoparticles in fluids have been extensively studied. In fluids with very low-particle concentration, the thermal performance of nanofluids will be significantly improved, which has been confirmed [19][20][21]. Das et al [22] reviewed the properties of nanofluid heat transfer enhancement, nanofluid preparation methods, and theoretical models based on the fluid delamination, particle aggregation, and particle motion, revealing that the thermal conductivity of nanofluids increases with increasing temperature.…”
Section: Introductionmentioning
confidence: 87%
“…Achieving optimal thermal performance in these systems is a fundamental objective, and emerging technologies offer promising solutions in this endeavor (Akyurek et al, 2018; Ceviz & Kaymaz, 2005). Energy systems and novel techniques investigated by scientists undergo thermal analysis, unveiling their potential for substantial improvements in heat transfer, energy conversion, and management (Akyurek et al, 2022; Arzutuğ, 2023; Sahin et al, 2016). Utilizing these technologies provides a promising pathway to enhance energy systems, elevating their efficiency, sustainability, and overall performance in the dynamic realm of scientific progress (Akyurek & Yoladi, 2021; Subasi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%